Navigating the Disruption: A Bibliometric Analysis of Generative AI in Accounting Education Research (2022-2025) - Irvan Bravely; Harmiati Hatta; Zoel Dirga Dinhi; A. Nursyamsi Amin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
Purpose: The rapid development of Generative AI (GenAI), particularly following the launch of ChatGPT in 2022, has triggered significant disruption in global higher education. In accounting education, this technology presents complex challenges regarding academic integrity and information accuracy, while also offering significant opportunities to personalize learning and enhance operational efficiency. This study aims to conduct a bibliometric analysis to visualize the evolution of research, identify key contributors, and map critical themes in GenAI and accounting education from 2022 to 2025. Research Design and Methodology: This study uses a bibliometric approach to integrate performance analysis and science mapping. Fifty-eight Scopus-indexed documents were analyzed via VOSviewer and Bibliometrix. Key visualization techniques, including co-authorship, co-citation, keyword co-occurrence, and topic modeling, were applied to identify and map dominant research themes. Findings and Discussion: A publication surge with an 87.58% annual growth rate. Southeast Asian nations (Indonesia, Malaysia, Vietnam) have emerged as major contributors, rivaling Western output on GenAI integration in accounting. Thematic analysis identifies a shift in focus from technical aspects to student competencies such as critical thinking, AI literacy, and adaptive assessment. Identifying the Journal of Accounting Education and Issues in Accounting Education as core references bridging pedagogy and technology, this study provides a roadmap for curricular reform in the Industry 4.0 era. Implications: GenAI integration forces a redefinition of graduate competencies amidst rapid literary expansion. The focus is shifting from procedural mastery to educational psychology, ethics, and human-machine collaboration to prevent the erosion of foundational skills. Ultimately, successful transformation depends on curriculum developers embedding digital literacy to maintain graduate relevance in the Society 5.0 landscape.